A distribuição das receitas e dos gastos entre os niveis de governo e o desiquilibrio das contas publicas federais - Meirelles, Durval Correa (1995)
This research tries to identify the link between distributing expenses and the public budget between leveIs of governrnent, and the financiaI unbalance that has taken over the federal governrnent. This research tries to show the historical evolution of the tax and tariff distribution in Brazil, always relating it to the increase of the national debt. In an embrionary way this research analyses the debate over the governrnents job in controlling the econorny, and the I I participation of the actors involved and their proposals to reduce the public deficit, and, consequently, the national debt.